A study on the right to give consent to treatment by a mental health patient in Malaysia: comparative analysis between the mental disorder ordinance 1952 and the mental health act 2001 / Adi Aizat Yajid ...[et al.] - Yajid, Adi Aizat; Shamshudin, Mohd Khairunnizam; Megat Mohd Ghazali, Megat Aiman Taher; Sofian @ Mohd Sofi, Noor Azam (2009)
Normally the mental health patients would be considered incapable of managing themselves because of their illness. There have to be someone to help them in their daily life. Their status as mental health patients gives rise to problems in the case of treatment. In general, treatments cannot be carried out without the consent from the patients. But would the situation be different for mental health patients still a question that need to be figured out since the answer is not that clear. This project paper will focus on the rights of giving consent by the mental health patients and their rights over their body integrity. An analysis will be made by comparing the Malaysian Mental Disorder Ordinance 1952 and the Mental Health Act 2001. The paper will also discuss the comparison between both Malaysian law and the United Kingdom Mental Health Act 2007. At the end of the discussion, analysis on the current practice over the procedures that are carried out in order to gain consent from the mental health patients will be formulated.